Biobased ionic liquids as solvents of paramylon - Feuzing, Frédérica; Mbakidi, Jean-Pierre; Lazar, Florica; Marchal, Luc; Leroy, Eric; Bouquillon, Sandrine (Journal of Molecular Liquids, 2023)
Paramylon is a linear glucan produced by Euglena gracilis microalgae as water insoluble intracellular granules. Its macromolecular structure contains only β(1–3) linkages, resulting in a stable triple helix conformation and a high crystallinity. It is soluble in very few solvents such as DMSO, harsh alkaline or acid solutions and imidazolium ionic liquids. In this paper we prepared biosourced more ecofriendly ionic liquids which can tolerate high amounts of water as a co-solvent and which are recyclable. The solubility of the paramylon was then evaluated depending of the nature of the ionic liquid and the structure and thermal properties of the biopolymer before and after solubilisation and regeneration were also discussed.
Keywords: Amino acids; Choline; Ionic liquids; Microalgae; Paramylon; Solubility